Development of linear proton accelerators with the high average beam power - Bomko, V.A.; Zajtzev, B.V.; Egorov, A.M. (Вопросы атомной науки и техники, 2001)
Review of the current situation in the development of powerful linear proton accelerators carried out in many countries is given. The purpose of their creation is solving problems of safe and efficient nuclear energetics on a basis of the accelerator-reactor complex. In this case a proton beam with the energy up to 1 GeV, the average current of 30 mA is required. At the same time there is a needed in more powerful beams, for example, for production of tritium and transmutation of nuclear waste products. The creation of accelerators of such a power will be followed by the construction of linear accelerators of 1 GeV but with a more moderate beam current. They are intended for investigation of many aspects of neutron physics and neutron engineering. Problems in the creation of efficient constructions for the basic and auxiliary equipment, the reliability of the systems, and minimization of the beam losses in the process of acceleration will be solved.